SD DENGUE DUO® (NS1, IgG, IgM) RAPID TEST DALAM MENUNJANG DIAGNOSIS INFEKSI VIRUS DENGUE - Diah Puspita Rini; Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Dengue virus infection can cause dengue hemorrhagic fever (DHF) which is still a major health problem in Indonesia. Thediagnosis of DHF is established based on WHO criteria and IgM/IgG antidengue serologic markers. A rapid method is needed for thedetecting or screening the disease. Antigen detection (NS1) can be performed by immunochromatography (rapid test) or enzyme -linkedimmunosorbent assay (ELISA). Recently, a rapid test to detect NS1 as an antigen and IgM/IgG antidengue to differentiate primary andsecondary dengue virus infection is available in one cassette. This study evaluated the new commercial dengue rapid test, SD DengueDuo for the detection of both antigen and antibodies to dengue virus. Serum samples used in this study were collected from 33 denguevirus infection patients according to WHO criteria and admitted in the Tropical Ward, Dr. Soetomo Hospital. Samples were taken twice,during acute and convalescent phase. SD Dengue Duo (NS1, IgG, IgM) rapid test was used and confirmed by ELISA as the gold standard.To determine the diagnostic specificity 20 samples of non dengue virus infection (typhoid fever and malaria) confirmed by laboratorytests were used. In the acute phase, SD Dengue Duo (NS1, IgG, IgM) rapid test showed IgG sensitivity 94.7% (18/19), specificity 92.9%(13/14), IgM sensitivity 85% (17/20), specificity 100% (13/13), NS1 sensitivity 50% (10/20), specificity 100% (13/13). In theconvalescent phase, SD Dengue Duo (NS1, IgG, IgM) rapid test showed antidengue IgG sensitivity 96.3% (26/27), specificity 66.7%(4/6), IgM sensitivity 95% (22/23), specificity 80% (8/10), NS1 sensitivity 42.9% (3/7), specificity 100% (26/26). To establish thediagnosis of dengue virus infection, not only NS1, but also antidengue IgM/IgG is needed. SD Dengue Duo containing dengue NS1 antigencombined with IgG/IgM test in one cassette is a rapid, practical and has a high validity diagnostic result.